Effectiveness of Social Marketing Campaign in Increasing Sales of Local Products in Lebosari - Hani Nur Endah; Abdi Hannan; Achmad Luthfun Nada; Septy Aisah; Iffah Syafaatul Arabia; Rosa Ezizya Febriani; Mauidzah Khasanah; Takat Ardisuma Cahya; Putri Misjayanti; Lainatul Mudzkiyyah (Universitas Kristen Indonesia Toraja, 2024)
The use of social media has revolutionized consumer behavior and the way companies operate their businesses. Digital and social marketing provides a great opportunity for organizations by offering lower costs and increased sales. This study aims to explore effective marketing methods in driving sales growth through the use of social media. This study was conducted on food products that have received halal certification and labels from MSMEs in Lebosari, Kendal. This study applies a qualitative approach through a case study method. Data were collected through interviews with MSME actors. The results of the study revealed that there was no increase in sales after the digital marketing seminar held two weeks ago. The strategy implemented remains focused on selling products directly at stalls, without significant changes towards online marketing. This study is limited to the minimal use of social media by MSME actors, who generally choose free platforms for marketing. This study highlights the relationship between marketing strategies, increased sales, and the importance of social media, halal products to be more competitive